Health-related quality of life in patients with lower limb amputation – an assessment of the measurement properties of EQ-5D-3L and EQ-5D-5L using data from the Swedish Amputation and Prosthetics Registry. Issue 26 (18th December 2022) - Ernstsson, Olivia; Hagberg, Kerstin; Janssen, Mathieu F.; Bonsel, Gouke J.; Korkmaz, Seher; Zethraeus, Niklas; Heintz, Emelie
Abstract: Purpose: To assess the measurement properties of EQ-5D-3L and EQ-5D-5L in patients with a major lower limb amputation (LLA). Methods: This was a retrospective register-based study using data from the Swedish Amputation and Prosthetics Registry (SwedeAmp). Patients with a six-months follow-up (including either EQ-5D-3L or EQ-5D-5L) after a major unilateral LLA were included. The measurement properties of EQ-5D-3L and EQ-5D-5L were compared in terms of feasibility, response patterns, informativity, and convergent and known-group validity. Results: The sample included 700 patients with below-knee amputation (76%), above-knee amputation (18%), or knee disarticulation (7%). Responses to EQ-5D-3L and −5L were similar regarding feasibility (98% completion rate) and the proportion reporting no problems (7% and 6%). Compared to EQ-5D-3L, EQ-5D-5L showed higher absolute and relative informativity in all dimensions, with the largest improvement in the mobility dimension. In the analyses of convergent validity, the EQ-5D-5L generally showed stronger correlations with disease-specific measures. Only EQ-5D-5L was able to discriminate between subgroups with different amputation levels. Conclusion: The findings support the use of EQ-5D-5L over EQ-5D-3L in patients with an LLA, mainly due to improved informativity and improved convergent and known-group validity. Implications for rehabilitation: The measurement properties of two EQ-5D versions, EQ-5D-3L and EQ-5D-5L, has so far not been evaluated in patients with a lower limb amputation (LLA) The results support the use of EQ-5D-5L over the use of EQ-5D-3L, mainly due to improved informativity and stronger correlations with disease-specific patient-reported outcome measures The five-level version of EQ-5D is recommended for future applications of EQ-5D in clinical outcome studies, health economic evaluations, and in the routine follow-up of patients with a major LLA In the early rehabilitation process six months after an LLA, the majority of patients reported problems with mobility, pain/discomfort, and usual activities